Rift Valley fever/malaria study site analysis and major findings for Rift Valley fever and malaria transmission - Bett, Bernard K.; Gachohi, John M.; Mbotha, D. (2013)
This deliverable gives provisional results of the on-going analyses on RVF and malaria transmission studies in Kenya. Analyses on RVF are based on historical data on RVF outbreaks recorded in the study site between 1961 and 2007, initial outputs from the RVF dynamical model that is being developed, and data collected from participatory studies. All the analyses on malaria are based on hospital records covering the period 2006 – 2011.